Starch / resin-based composite hard carbon material as well as preparation method and application thereof
By foaming and crosslinking and sintering the starch and resin-based composite hardcarbon materials, starch/resin-based composite hardcarbon materials are prepared, which solves the problems of high preparation costs and limited rate performance of existing materials, and achieves cost reduction and electrochemical performance improvement.
Patent Information
- Application Number
- CN202411801906.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
The existing resin-based hard carbon materials have high preparation costs and limited rate performance, making it difficult to meet the market's demand for high energy density and fast charging sodium ion battery materials.
The starch/resin-based composite hardchar material is prepared by the mixing and sintering process of foamed crosslinked starch and resin precursor to form a starch/resin-based composite hardchar material. The method includes the steps of starch foaming cross-linking, resin heating curing, mixed ball milling and two sintering.
It reduces the cost of material preparation, improves electrochemical performance, especially in terms of rate performance, and is suitable for fast rechargeable batteries and has good application prospects.
Smart Images

Figure CN119650635A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary battery material preparation, and in particular relates to a starch / resin-based composite hard carbon material and a preparation method and application thereof. Background Art
[0002] Hard carbon is a kind of amorphous carbon that is difficult to graphitize even at temperatures above 2500°C. Hard carbon is generally made by high-temperature carbonization of oxygen-rich substances such as biomass, resin, and coal as precursors. Due to its large specific surface area, it has good adsorption properties and can be used in water treatment, air purification and other fields as an adsorbent or catalyst carrier; it has a rich pore structure inside, which further enhances its adsorption and catalytic properties; it has excellent electrical conductivity and can be used as electrode materials, capacitors and other electronic components; secondly, hard carbon is chemically inert and not easy to react with other substances, which gives it advantages in applications such as catalyst carriers; when used as fuel, hard carbon has a high calorific value, high combustion efficiency, and produces less ash, which is suitable for various combustion equipment; therefore, it has a wide range of applications in the fuel field, chemical field and material field.
[0003] As a high-performance electrode material, resin-based hard carbon has shown great potential and advantages in the field of battery technology. Its unique physical and chemical properties give it extremely high charge and discharge capacity, which means that at the same volume or weight, batteries using resin-based hard carbon can store and release more electrical energy. This is crucial for improving the energy density of batteries, which is directly related to longer battery life and more efficient energy utilization of devices. What is even more valuable is that resin-based hard carbon can still maintain a relatively high capacity retention rate after multiple charge and discharge cycles, which reflects its excellent cycle stability. In the fields of electric vehicles, energy storage systems, etc., batteries need to withstand thousands of charge and discharge cycles, and this characteristic of resin-based hard carbon undoubtedly provides a solid foundation for extending the overall service life of the battery, while also greatly reducing the cost caused by frequent battery replacement. In view of the above significant advantages, resin-based hard carbon is highly favored in the selection of battery materials, especially in the two major mainstream systems of sodium-ion batteries and lithium-ion batteries. Sodium-ion batteries have attracted much attention due to their low cost and abundant resources, while lithium-ion batteries are famous for their high energy density and wide application base. Resin-based hard carbon can not only meet the technical requirements of these two battery systems, but also further promote their innovation and development in new energy vehicles, portable electronic devices, large-scale energy storage and other fields. In summary, resin-based hard carbon has broad application prospects and unlimited development potential in the battery field due to its excellent performance in many aspects.
[0004] As a precursor of hard carbon materials, resin-based materials have a series of advantages such as batch stability, high specific capacity, and high initial efficiency. However, the high cost of resin-based precursors and the limited rate performance of finished products restrict the development of resin-based hard carbon. With the market demand for high energy density and fast-charging sodium-ion battery materials, the development of a resin / starch composite negative electrode modified hard carbon material with low cost, high specific capacity, and good rate performance has good application prospects. Summary of the invention
[0005] The object of the present invention is to provide a starch / resin-based composite hard carbon material and a preparation method and application thereof, so as to solve the technical problem of high cost of existing material preparation.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a starch / resin-based composite hard carbon material, comprising the following steps: The starch is mixed with the additives for foaming and cross-linking to obtain a starch precursor; the resin, the curing agent, the solvent and the modifier are mixed and heated and cured to obtain a resin precursor; After mixing the starch precursor with the resin precursor, a precursor material is obtained; After the precursor material is sintered twice, a starch / resin-based composite hard carbon material is obtained.
[0007] Furthermore, the starch is at least one of corn starch, potato starch, cassava starch, rice starch, bean starch and cereal starch; and the additive is one or more of diaminoethanol, glyoxal and glutaraldehyde.
[0008] Furthermore, the resin is one or more of acrylic resin, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, sugar alcohol resin, polyester resin and polyamide resin; the solvent is one or more of water, ethanol, polyethylene glycol and isopropanol.
[0009] Furthermore, the curing agent is one or more of aliphatic amines, alicyclic amines, aromatic amines, polyamides and various acid anhydrides; the modifier is one or more of phosphoric acid, potassium dihydrogen phosphate, manganese chloride, boric acid and ammonium chloride.
[0010] Furthermore, the mass ratio of the starch to the additive is (5-10):1.
[0011] Furthermore, the mass ratio of the resin to the solvent is (1-4):1; the mass ratio of the resin to the curing agent is (1-10):1; the mass ratio of the resin to the modifier is (50-100):1; The temperature of the heating curing is 150°C to 250°C.
[0012] Furthermore, the starch precursor and the resin precursor are mixed by ball milling; the rotation speed of the ball milling is 300-400 r / min, and the time is 4h-8h; and the ball milling further includes screening after the mixing.
[0013] Furthermore, the two sintering processes are to first pre-sinter the precursor material at 500-700°C, obtain a pre-sintered product after screening, and then sinter the pre-sintered product at a high temperature of 1200-1400°C and keep it warm for 2-6 hours.
[0014] The invention also discloses a starch / resin-based composite hard carbon material prepared by the preparation method.
[0015] The invention also discloses application of the starch / resin-based composite hard carbon material in a sodium ion battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a starch / resin-based composite hard carbon material. Starch is foamed and cross-linked and then added to a resin-based hard carbon material. The starch optimizes the surface of the original hard carbon material and forms new functional group adsorption. The cost of the starch raw material is one tenth of that of the resin, thereby reducing the cost of the resin-based hard carbon and improving the electrochemical performance. The present invention dopes different starches in order to maintain the excellent specific capacity and first effect of the resin-based hard carbon while reducing the cost.
[0017] Furthermore, after adding foamed cross-linked starch, the small molecules in the starch filled the micropores, invalid pores, and open pores of the resin-based hard carbon, achieving the pore structure regulation of the hard carbon and preparing microporous-free hard carbon. The hard carbon has excellent rate performance and has good application prospects in fast-charging batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the starch / resin-based composite hard carbon material prepared in Example 1 of the present invention; Figure 2 The button-type battery cycle curves of the composite hard carbon materials prepared in Examples 1 to 5 and Comparative 1; Figure 3 The charging rate performance of button-type batteries assembled from the composite hard carbon materials prepared in Examples 1 to 5 and Comparative Example 1. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0025] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0026] Example 1 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g corn starch and 5g diaminoethanol were mixed, mechanically stirred and put into a tube furnace, kept at 250°C for 6h under argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g maleic anhydride was dissolved in 20g ethanol, 40g phenolic resin and 0.6g phosphoric acid were added and stirred evenly in a magnetic stirrer, and placed in a blast drying oven at 180°C for heating and curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 600° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1200° C. for 6 hours to obtain a starch / resin-based composite hard carbon material.
[0027] Example 2 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of potato starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven for heating and curing at 200°C, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 600° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1300° C. for 4 hours to obtain a starch / resin-based composite hard carbon material.
[0028] Example 3 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of cassava starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven and heated at 220°C for curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 600° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1400° C. for 2 hours to obtain a starch / resin-based composite hard carbon material.
[0029] Example 4 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of rice starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven and heated and cured at 220°C, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 600° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1200° C. for 2 hours to obtain a starch / resin-based composite hard carbon material.
[0030] Example 5 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of bean starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven and heated at 220°C for curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 500° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1200° C. for 2 hours to obtain a starch / resin-based composite hard carbon material.
[0031] Example 6 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of cassava starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven and heated at 220°C for curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 600° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1400° C. for 2 hours to obtain a starch / resin-based composite hard carbon material.
[0032] Example 7 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of cassava starch and 5g of diaminoethanol were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of phenolic resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven and heated at 220°C for curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 4 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 700° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1200° C. for 2 hours to obtain a starch / resin-based composite hard carbon material.
[0033] Example 8 A method for preparing a starch / resin-based composite hard carbon material comprises the following steps: 50g of soybean starch and 10g of glutaraldehyde were mixed, mechanically stirred and then put into a tube furnace, kept at 250°C for 6h under an argon atmosphere, and the foamed starch was taken out and crushed to obtain a starch precursor; 2.22g of maleic anhydride was dissolved in 20g of ethanol, 40g of urea-formaldehyde resin and 0.6g of phosphoric acid were added and stirred evenly in a magnetic stirrer, and then put into a blast drying oven at 150°C for heating and curing, and the cured resin was taken out and crushed to obtain a resin precursor; 3 g of starch precursor and 10 g of resin precursor were ball-milled at a speed of 400 r / min for 8 h; the obtained mixture was sieved through a 150-mesh sieve to obtain a precursor material; The precursor material is pre-sintered at 500° C. to obtain a pre-sintered product; the pre-sintered product is kept at 1300° C. for 6 hours to obtain a starch / resin-based composite hard carbon material.
[0034] Comparative Example 1 This comparative example provides a resin / starch-based hard carbon composite material, and the specific implementation manner is the same as that of Example 1, except that the corn starch is not subjected to foaming treatment.
[0035] Comparative Example 2 This comparative example provides a resin / starch-based hard carbon composite material, and the specific implementation manner is the same as that of Example 2, except that the resin is mixed with potato foamed starch and then cured.
[0036] Comparative Example 3 This comparative example provides a resin / starch-based hard carbon composite material, and the specific implementation manner is the same as that of Example 3, except that the mixing ratio of the resin precursor to the cassava starch precursor is 1:1.
[0037] Figure 1 This is a SEM image of the starch / resin-based composite hard carbon material prepared in Example 1 of the present invention. From the image, it can be seen that the hard carbon material has an irregular shape and a relatively uniform particle size distribution, with the particle sizes mostly distributed in the range of 5 μm to 10 μm.
[0038] The interlayer spacing, specific surface area, and particle size D50 of the composite hard carbon materials in Examples 1 to 5 and Comparative Examples 1 to 3 were measured according to the method of the national standard GBT-24533-2019 "Graphite Negative Electrode Materials for Lithium-ion Batteries".
[0039] Table 1 Performance test data of different composite hard carbon materials
[0040] As can be seen from Table 1, the embodiments have better electrochemical performance than the comparative examples. According to comparative example 1, after starch foaming treatment, the electrochemical performance of hard carbon mixed with resin is significantly improved, and the coulomb efficiency of embodiment 1 can reach nearly 90%, and starch foaming has a better effect of modifying the surface; the first discharge capacity of comparative example 2 is lower than that of embodiment 2, and the resin is first solidified and then mixed with starch, which is more conducive to the formation of sodium storage sites; and after increasing the starch mixing ratio in comparative example 3, the first discharge capacity and the first coulomb efficiency of hard carbon both decrease, indicating that starch should not be added excessively.
[0041] The composite hard carbon materials in Examples 1 to 5 and Comparative Examples 1-3 are used as negative electrode materials for sodium ion batteries and assembled into button cells. The specific preparation method of the negative electrode material is as follows: the mass of the hard carbon composite material: CMC:SBR:SP is mixed in a mass ratio of 8:0.4:0.6:1 to prepare a negative electrode sheet, and the sodium sheet is the counter electrode; the electrolyte uses 1.0 M NaPF6 in EC:DMC; EMC=1:1:1Vol%, and the diaphragm uses a glass fiber diaphragm. The button cell is assembled in an argon-filled glove box. The electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester. The charge and discharge voltage range was 0V to 3V, and the rate performance test selected 1C and 10C. The test results are as follows Figure 2 and Figure 3 shown.
[0042] from Figure 2 and Figure 3 It can be seen that the mixed hard carbon has good cycle performance and rate performance. After 70 cycles, the specific capacity remains at 300 mAh / h. At the same time, at a high current discharge of 10C, the material still has a specific capacity of 275 mAh / h.
[0043] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a starch / resin-based composite hard carbon material, characterized in that: The following steps are involved: The starch is mixed with the additives for foaming and cross-linking to obtain a starch precursor; the resin, the curing agent, the solvent and the modifier are mixed and heated and cured to obtain a resin precursor; After mixing the starch precursor with the resin precursor, a precursor material is obtained; After the precursor material is sintered twice, a starch / resin-based composite hard carbon material is obtained.
2. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The starch is at least one of corn starch, potato starch, cassava starch, rice starch, soybean starch and cereal starch; and the additive is one or more of diaminoethanol, glyoxal and glutaraldehyde.
3. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The resin is one or more of acrylic resin, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, sugar alcohol resin, polyester resin and polyamide resin; the solvent is one or more of water, ethanol, polyethylene glycol and isopropanol.
4. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The curing agent is one or more of aliphatic amine, alicyclic amine, aromatic amine, polyamide and maleic anhydride; the modifier is one or more of phosphoric acid, potassium dihydrogen phosphate, manganese chloride, boric acid and ammonium chloride.
5. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The mass ratio of the starch to the additive is (5-10):
1.
6. The method for preparing a resin-based hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the resin to the solvent is (1-4):1; the mass ratio of the resin to the curing agent is (1-10):1; the mass ratio of the resin to the modifier is (50-100):1; The temperature of the heating curing is 150°C to 250°C.
7. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The starch precursor and the resin precursor are mixed by ball milling; the rotation speed of the ball milling is 300-400 r / min, and the time is 4h-8h; and the ball milling further includes screening after the mixing.
8. The method for preparing a starch / resin-based composite hard carbon material according to claim 1, characterized in that: The two sintering processes are to pre-sinter the precursor material at 500-700°C first, obtain the pre-sintered product after screening, and then sinter the pre-sintered product at 1200-1400°C for high temperature sintering and keep the temperature for 2-6 hours.
9. A starch / resin-based composite hard carbon material, characterized in that: The method is prepared by any one of claims 1 to 7.
10. Use of the starch / resin-based composite hard carbon material according to claim 9 in sodium ion batteries.